A Study of the Laser-Induced Breakdown Spectroscopy of Carbon in the Ultraviolet Wavelength Range Under Vacuum Conditions *supported by the National Special Fund for the Development of Major Research Equipment and Instruments of China (No. 2014YQ120351). (August 2015) - Pan, Congyuan; Du, Xuewei; Zeng, Qiang; Yu, Yunsi; Wang, Shengbo; Wang, Qiuping
Abstract The influence of a vacuum on the laser-induced breakdown spectroscopy (LIBS) of carbon in the ultraviolet wavelength range is studied. Experiments are performed with graphite using a LIBS system, which consists of a 1064 nm Nd:YAG laser, a vacuum pump, a spectrometer and a vacuum chamber. The vacuum varies from 10 Pa to 1 atm. Atomic lines as well as singly and doubly charged ions are confirmed under the vacuums. A temporal evolution analysis of intensity is performed for the atomic lines of C I 193.09 nm and C I 247.86 nm under different vacuum conditions. Both time-integrated and time-resolved intensity evolutions under vacuums are achieved. The lifetimes of the two atomic lines have similar trends, which supports the point of view of a 'soft spot'. Variations of plasma temperature and electron density under different vacuums are measured. This study is helpful for research on carbon detection using LIBS under vacuum conditions.